Randomized prospective study of three different techniques for ultrasound-guided axillary brachial plexus block - Ferraro,Leonardo Henirque Cunha (2018)
Abstract Introduction Randomized prospective study comparing two perivascular techniques with the perineural technique for ultrasound-guided axillary brachial plexus block (US-ABPB). The primary objective was to verify if these perivascular techniques are noninferior to the perineural technique. Method 240 patients were randomized to receive the techniques: below the artery (BA), around the artery (AA) or perineural (PN). The anesthetic volume used was 40 mL of 0.375% bupivacaine. All patients received a musculocutaneous nerve blockade with 10 mL. In BA technique, 30 mL were injected below the axillary artery. In AA technique, 7.5 mL were injected at 4 points around the artery. In PN technique, the median, ulnar, and radial nerves were anesthetized with 10 mL per nerve. Results Confidence interval analysis showed that the perivascular techniques studied were not inferior to the perineural technique. The time to perform the blockade was shorter for the BA technique (300.4 ± 78.4 s, 396.5 ± 117.1 s, 487.6 ± 172.6 s, respectively). The PN technique showed a lower latency time (PN - 655.3 ± 348.9 s; BA - 1044 ± 389.5 s; AA - 932.9 ± 314.5 s), and less total time for the procedure (PN - 1132 ± 395.8 s; BA - 1346.2 ± 413.4 s; AA - 1329.5 ± 344.4 s). BA technique had a higher incidence of vascular puncture (BA - 22.5%; AA - 16.3%; PN - 5%). Conclusion The perivascular techniques are viable alternatives to perineural technique for US-ABPB. There is a higher incidence of vascular puncture associated with the BA technique.